Transport Stress Mitigation and the Effects of Preanesthesia on Striped Bass. (14th December 2018) - Kenter, Linas W.; Gunn, Mackenzie A.; Berlinsky, David L.
Abstract: The demand for Striped Bass Morone saxatilis as food and sport fish has generated interest in developing effective transport and handling protocols. Studies have shown that anesthetics and elevated salinity can reduce transport stress in Striped Bass, but no studies have compared stress responses among strains or compared and combined treatments to maximize efficacy. In this study, 1‐h transport trials were conducted with subadults produced from wild‐caught (Florida strain) and domesticated Striped Bass. Fish were transported in freshwater (FW; 0‰) or brackish water (SW; 10‰) alone or containing either metomidate hydrochloride (hereafter, "metomidate"; 1 mg/L) or tricaine methanesulfonate (MS‐222; 25 mg/L). After transport, half the fish from each treatment were sampled for cortisol or stocked in a freshwater recirculating system to monitor their health and behavior for 7 d. In preanesthesia trials, Florida‐strain fish were netted and transferred to baths containing a single anesthetic (induction doses; 5‐mg/L metomidate or 150‐mg/L MS‐222), observed for nociception and recovery, and bled 1 h after anesthesia for cortisol analysis. Results from this traditional approach were compared to results for fish that were first exposed to low anesthetic doses (1‐mg/L metomidate or 25‐mg/L MS‐222) added directly to the culture tank prior to netting and then were transferred to baths containing induction doses of the same anesthetic. In transport studies, cortisol was elevated in the MS‐222 and FW treatment groups compared to the metomidate and SW treatment groups, respectively. Strain, feed consumption, and health were not correlated with cortisol measured following the transport stressor. In the preanesthesia study, metomidate blocked cortisol synthesis if added prior to or following handling, while MS‐222 blocked nociception.